PENGARUH KUALITAS PELAYANAN, PENGETAHUAN DAN SANKSI PERPAJAKAN PADA KEPATUHAN WAJIB PAJAK BADAN - Paramartha, I Putu Indra Pradnya; Rasmini, Ni Ketut (E-Jurnal Akuntansi; Vol 15 No 1 (2016), 2016)
The aim of this study was to determine the effect of service quality, knowledge and tax penalties on taxpayer compliance. The study was conducted at the Tax Office (KPP) Primary Gianyar 2015. Samples were selected using a formula slovin. Data was collected by distributing questionnaires to effective corporate taxpayers registered in STO Gianyar and techniques of analysis using multiple linear regression analysis. Based on the analysis, it is known that the quality of service, knowledge and sanction tax positive effect on taxpayer compliance. Variable quality of service, knowledge and tax penalties affect taxpayer compliance by 81.3 percent, while the remaining 18.7 percent is influenced by other variables not included in the research model.
Keywords: Quality of Service, Tax Knowledge, Sanctions Taxation, Taxpayer Compliance